TRANSCENDING THE SONIC AND THE TEXTUAL - Njoku, Obianuju Akunna (International Library of African Music, 2023)
Among Muslim women in predominantly Islamic societies, music-making remains a contested subject. At the core of these contestations are questions of boundaries, agency, taboos, resistance, and generalisations of the socio-musical experiences of Muslim women. This article explores the development of senwele music, a socio-religious music form of the Ilorin in northern Nigeria, from its origin as orin-kengbe (calabash music) to its transition into a translocal music form. Given influences of the Yoruba, Hausa-Fulani, and Islam, senwele music is examined as a compendium of history; one that is not only reflective of the Ilorin traditional music scene, but also the north-south dualism in Ilorin, tensions in music-making and Islam, and regio-political remapping in Nigeria. Based on fieldwork with a major exponent of senwele, Alhaja Iya Aladuke, and her music group in Ilorin, the article explores the practice, ambivalences, convivialities and sustainability of senwele music performance within its predominantly Islamic context. I argue that while established societal conventions, such as those in Ilorin, function as a standard for the acceptance of music, a woman musician such as Alhaja Iya Aladuke continues to thrive through a musician-community exchange that takes into cognisance the sensibilities of the people while retaining their patronage and her artistic autonomy. Beyond its sonic, textual, and entertainment prerogatives, the sustained practice of senwele music in Ilorin presents a continuum for interrogating and negotiating cross-cultural encounters, socio-religious binaries, gender boundaries, and the multiplicity in the socio-musical experiences of Muslim women.
Keywords: Music; Women; Yoruba (African people); Women musicians; Musicians; Islamic music; Yoruba Art; Hausa-Fulani; Ilorin; Nigeria; Orin-kengbe (Music); Muslim Women; Senwele (Music); African Music